Hierarchical fibrillar scaffolds obtained by non-conventional layer-by-layer electrostatic self-assembly - Oliveira, Sara M. (2012)
A new approach of layer-by-layer assembling is disclosed, able to create nano/micro fibrils or nanocoatings inside 3D scaffolds using non-fibrils polyelectrolytes for tissue engineering applications. This approach shows to be promising for develop advanced scaffolds with controlled nano/micro environment, nature and architecture similar to natural extracellular matrix, with improved biological performance.